Physicians' perceptions and preferences for implementing venous thromboembolism (VTE) clinical practice guidelines: a qualitative study using the Theoretical Domains Framework (TDF) - Juliana Abboud; Abir Abdel Rahman; Niaz Shaikh; Martin Dempster; Pauline Adair (BMC, 2022)
Abstract Background Venous thromboembolism is a primary cause of morbidity and mortality in hospitalised patients. Clinical practice guidelines were developed to prevent venous thromboembolism events. This study adopted the Theoretical Domains Framework to explore the beliefs and perceptions of physicians adoption of clinical practice guidelines for the uptake of venous thromboembolism prevention guidelines. Methods Semi-structured interviews were conducted with a stratified purposive sample of internal medicine physicians in an acute hospital. The interview topic guide was developed using the Theoretical Domains Framework to identify the factors perceived to influence the practice. Two researchers coded the interview transcripts using thematic content analysis. Emerging relevant themes were mapped to TDF domains. Results A total of sixteen medical physicians were interviewed over a six-month period. Nine theoretical domains derived from thirty-three belief statements were identified as relevant to the target behaviour; knowledge (education about the importance of VTE guidelines); beliefs about capabilities (with practice VTE tool easier to implement); beliefs about consequences (positive consequences in reducing the development of VTE, length of stay, financial burden and support physician decision) and (negative consequence risk of bleeding); reinforcement (recognition and continuous reminders); goals (patient safety goal); environmental context and resources (workload and availability of medications were barriers, VTE coordinator and electronic medical record were enablers); social influences (senior physicians and patient/family influence the VTE practice); behavioural regulation (monitoring and mandatory hospital policy); and nature of the behaviour. Conclusions Using the Theoretical Domains Framework, factors thought to influence the implementation of VTE clinical practice guidelines were identified which can be used to design theoretically based interventions by targeting specific psychological constructs and linking them to behaviour change techniques to change the clinical practice of physicians.